الجماعات الطلابية وكيفيات تأسيسها في الوسط الجامعي دراسة ميدانية على طلبة جامعة الجزائر 2 - قايد, الأستاذ: عادل (Sciences de l'Homme et de la Société, 2015)
يهدف هذا البحث إلى إبراز أهم العوامل النفسية، والاجتماعية، والثقافية التي تدفع الطلبة إلى تأسيس جماعات طلابية في جامعة الجزائر2. وقد أشرنا في الدراسة إلى دور الجهوية، اللهجة، التخصص الدراسي، المصلحة المشتركة، بالإضافة إلى عوامل أخرى يمكن أن توضح لنا كيفية تأسيس جماعات الطلبة في جامعة الجزائر 2. والنتائج التي توصل إليها الباحث تشير إلى الأهمية التي تكتسيها الجهوية في تأسيس الجماعات الطلابية.   Abstract : This research aims to highlight the most important psychological factors, social, and cultural, which leads the students to the formation of student groups at the University of Algeria 2. We have referred in the study to the regional role, tone, academic specialization, the common interest, as well as other factors that could explain to us how to form groups of students at the University of Algeria 2. The findings of the researcher refers to the importance of regionalization in the formation of student groups.